2018
DOI: 10.1016/j.neuroimage.2018.01.075
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic resting state fMRI analysis in mice reveals a set of Quasi-Periodic Patterns and illustrates their relationship with the global signal

Abstract: Time-resolved 'dynamic' over whole-period 'static' analysis of low frequency (LF) blood-oxygen level dependent (BOLD) fluctuations provides many additional insights into the macroscale organization and dynamics of neural activity. Although there has been considerable advancement in the development of mouse resting state fMRI (rsfMRI), very little remains known about its dynamic repertoire. Here, we report for the first time the detection of a set of recurring spatiotemporal Quasi-Periodic Patterns (QPPs) in mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
98
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(116 citation statements)
references
References 105 publications
18
98
0
Order By: Relevance
“…Our study reproduces previous reports of the presence of reliably recurring quasi-periodic patterns in the brain (Belloy et al 2018;Majeed et al 2011;Thompson et al 2014;Yousefi et al 2018). This is the first time QPPs have been examined in whole-brain data from task-performing individuals.…”
Section: Fc Changessupporting
confidence: 93%
See 1 more Smart Citation
“…Our study reproduces previous reports of the presence of reliably recurring quasi-periodic patterns in the brain (Belloy et al 2018;Majeed et al 2011;Thompson et al 2014;Yousefi et al 2018). This is the first time QPPs have been examined in whole-brain data from task-performing individuals.…”
Section: Fc Changessupporting
confidence: 93%
“…Task performance drastically alters the functional architecture of the brain, shifting focus towards task-positive regions (Elton et al 2015;Goparaju et al 2014; Thompson et al 2013). So far, a detailed analysis of QPPs has only been conducted in anesthetized animals and resting-state humans (Belloy et al 2018;Majeed et al 2009;Majeed et al 2011;Thompson et al 2014b;Yousefi et al 2018). Task performance tends to increase anti-correlation between the DMN and TPN ), suggesting that QPP strength or frequency may be increased, altering measured functional connectivity as a result.…”
Section: -Introductionmentioning
confidence: 99%
“…We however noted that the anatomical organization of the unimodal-polymodal gradient was anatomically consistent with dominant recurring patterns of fMRI co-activation (CAPs) recently described to govern spontaneous fMRI network dynamics in this species 26,43 . These take the form of infraslow oscillatory transitions in latero-cortical and midline poly-modal regions reminiscent of the topographical organization of gradient A.…”
Section: Gradients Of Structural Connectivity Reflect Cortico-corticasupporting
confidence: 81%
“…Several studies have demonstrated that the functional state of the brain is dynamic over time, and this is reflected in functional connectivity changes 72,73 . These dynamic states are quantifiable, depend on the ongoing infraslow activity and seem to show atypical dynamics in some neurological disorders as autism 74 .…”
Section: Implications On Resting State Studiesmentioning
confidence: 99%